2021
DOI: 10.1088/1674-1137/ac1668
|View full text |Cite
|
Sign up to set email alerts
|

Instability of a black hole with f (R) global monopole under extended uncertainty principle *

Abstract: We consider the evolution of a black hole involving an f(R) global monopole based on the Extended Uncertainty Principle (EUP). The black hole evolutions refer to the instability due to the Parikh-Kraus-Wilczeck tunneling radiation or fragmentation. It is found that the EUP corrections make the entropy difference larger to encourage the black hole to radiate more significantly. We also show that the appearance of the EUP effects results in the black hole's division. The influence from the global monopole and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…where α is in unity, and L * is the large fundamental length scale counterpart of the Planck length l p . Thereafter, various authors considered exploring the effects of EUP on different black hole phenomena [56,[69][70][71][72][73][74][75][76]. Authors in Ref.…”
Section: Schwarzschild Black Hole Under Perturbationmentioning
confidence: 99%
“…where α is in unity, and L * is the large fundamental length scale counterpart of the Planck length l p . Thereafter, various authors considered exploring the effects of EUP on different black hole phenomena [56,[69][70][71][72][73][74][75][76]. Authors in Ref.…”
Section: Schwarzschild Black Hole Under Perturbationmentioning
confidence: 99%
“…It was found that the generalization of Heisenberg's uncertainty principle leads to the fragmentation of the f (R)-corrected black hole involving global monopole [20]. We generalize the consideration on the Hawking radiations and fragmentation of the black hole to the case under the extended uncertainty principle to show that the generalized uncertainty encourages the black hole instability referring to the Parikh-Kraus-Wilczeck tunneling radiation and division [21]. The observational appearances shown by three simple models of accretions of an f (R) global monopole black hole were studied [22].…”
mentioning
confidence: 91%
“…Since then, various studies have explored the black hole with EUP correction; see Refs. [23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%